A freestanding graphene oxide membrane for efficiently harvesting salinity gradient power. (November 2018) - Tong, Xin; Wang, Xin; Liu, Su; Gao, Haiping; Xu, Chunyan; Crittenden, John; Chen, Yongsheng
Abstract: Salinity gradient power (SGP) holds great potential for electricity generation. However, the technology scale-up is hindered by the lack of high-performance membranes. Here we initiate the application of freestanding graphene oxide membranes (GOMs) in pressure retarded osmosis (PRO) to generate SGP. The freestanding GOMs have moderate water permeability coefficient and excellent mechanical strength. Due to their ability to minimize internal concentration polarization (ICP), the freestanding GOMs can achieve high water flux in the osmosis systems, especially when the draw solution concentration is high. By combining experimental work and theoretical calculation, we found that the GOMs can have high power density in the PRO system: a power density of 24.62 W/m 2 is obtained at a hydraulic pressure of 6.90 bar using 3 M and 0.017 M of NaCl as a draw and a feed solution, respectively. This study provides a new way of designing membranes for PRO system, the results show great potential for application of GOMs in PRO to generate SGP. Graphical abstract: Image 1